1989
DOI: 10.3758/bf03334591
|View full text |Cite
|
Sign up to set email alerts
|

Expectation and satiation accounts of ambiguous figure-ground perception

Abstract: An expectancy account of figure-ground shifts, promoted as an alternative to satiation theory, was tested. One-hundred and three subjects in six conditions (Experiment 1) were either informed or uninformed about 12 to 13 ambiguous figures, and had either unlimited time or 30 sec in which to respond. In two of the conditions, head and eye movements were restricted, and in one condition, incidental learning was used. In keeping with an expectancy view, uninformed subjects saw fewer meaningful shapes than informe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Knowledge has been shown to affect perception in various modalities: Lindauer (1989) has shown that expectation alters ambiguous figure-ground perception; Van der Velde, Van der Heijden, and Schreuder (1989) have shown that knowledge affects visual word perception in context-dependent migration; Elman and McClelland (1988) have shown that knowledge in English affects speech perception with lexically restored phonemes; and Appelle and Countryman (1986) have shown that knowledge of the standard would reduce the haptic oblique effect. It appears that any theory in perception must be able to account for the effect of know1-edge on perception.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge has been shown to affect perception in various modalities: Lindauer (1989) has shown that expectation alters ambiguous figure-ground perception; Van der Velde, Van der Heijden, and Schreuder (1989) have shown that knowledge affects visual word perception in context-dependent migration; Elman and McClelland (1988) have shown that knowledge in English affects speech perception with lexically restored phonemes; and Appelle and Countryman (1986) have shown that knowledge of the standard would reduce the haptic oblique effect. It appears that any theory in perception must be able to account for the effect of know1-edge on perception.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reversal cannot be completely controlled or prevented from occurring. Two factors have been suggested to be causing perceptual reversal: 1 cognitive mechanisms such as attention and expectation, that allow the subject to bias her perception Chastain and Burnham 1975;Lindauer 1989;Riani et al 1984;Rock 1983;Rock and Mitchener 1992;Tsal and Kolbet 1985, and 2 neural satiation, which causes the representation of the currently dominant perception to gradually get weaker and eventually cause a switch A ttneave 1971; Babich and Standing 1981;Cornwell 1976;Long and Toppino 1981;Orbach et al 1963;Spitz and Lipman 1962. For the perceptual reversal experiment, two extensions to the basic VISOR architecture were made. Cognitive factors were modeled in VISOR by sending top-down input to the output unit of one of the schemas.…”
Section: Experiments 11: Robustness Against Impulse Noisementioning
confidence: 99%